PEMBANGUNAN BERKELANJUTAN BERBASIS POTENSI TEKNOLOGI, INOVASI, DAN PEMBERDAYAAN SOSIAL EKONOMI MASYARAKAT DI KABUPATEN LAMPUNG TENGAH - Suwandi, Suwandi; Meilinda, Selvi Diana (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2024)
The suboptimal use of information and technology systems for planning and monitoring, along with the lack of innovation and social empowerment programs by the Development Planning Agency at the Sub-National Level (Bappeda) of Central Lampung Regency, is indicated to potentially hinder the achievement of the Sustainable Development Goals (SDGs). This issue has drawn the author’s attention to propose ideas regarding the potential development of technology, innovation, and socio-economic empowerment to Bappeda of Central Lampung Regency. This study aims to explain the role of Bappeda in supporting sustainable development based on the potential, technology, innovation, and socio-economic empowerment of the community in Central Lampung Regency. By employing literature studies and descriptive analysis, document-based data relevant to the research focus were critically and thoroughly analyzed to obtain comprehensive answers to the research questions. The results indicate that Central Lampung Regency faces 15 strategic issues and six significant problems within Bappeda. The author suggests that the development of technology, innovation, and socio-economic empowerment can be achieved through collaborative efforts involving various stakeholders, ensuring that all processes are well-executed. It is hoped that the complexity of these problems can be addressed by maximizing the resources available in Central Lampung with support through several program initiatives aimed at achieving the sustainable development goals of Lampung Province by 2030.